Pengaruh Literasi Keuangan dan Kemudahan Penggunaan Terhadap Minat Menggunakan Aplikasi Paylater dengan Disonansi Kognitif sebagai Variabel Moderasi Pada Mahasiswa - Adianti, Tamaya; Purnomo, Arie Setyo Dwi (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
One phenomenon increasingly popular among students today is the use of paylater services. To use these services wisely, students need adequate financial literacy and a user-friendly application. This study aims to examine the influence of financial literacy and ease of use on the intention to use paylater applications, as well as the moderating role of cognitive dissonance.This research employs a quantitative approach with 100 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using Partial Least Squares (SmartPLS 4).The results show that financial literacy and ease of use have a positive and significant effect on the intention to use paylater services. However, cognitive dissonance does not moderate these relationships, likely because students use paylater for small transactions, which do not trigger internal conflict.